Development of Song Media Assisted with Canva To Improve the Acrostic Poetry Writing Skills - An-Nisa, Betha Centaury; Sutikno, Putri Yanuarita (research, training and philanthropy institution Natural Aceh, 2024)
This research aims to improve students' skills in writing acrostic poetry through the development of canva-assisted song media, in the form of an audio visual entitled